2012
DOI: 10.5751/es-04976-170401
|View full text |Cite
|
Sign up to set email alerts
|

Forestry and Road Development: Direct and Indirect Impacts from an Aboriginal Perspective.

Abstract: ABSTRACT. The forest industry is a significant contributor to the development of roads and most are constructed on Aboriginal territories. Many Aboriginal communities are isolated both socially and economically and Aboriginal cultures are often described as having inherent socio-environmental relationships. Aboriginal communities, therefore, may be the most likely to benefit and be most vulnerable to the impacts of road development. We use a case study approach to explore how an Aboriginal community interprets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…() with the Kitcisakik Nation in Quebec found concerns similar to those of Saulteau and West Moberly First Nations regarding the impacts of roads within culturally important territory. While modest research has examined in general the impacts of roads in various landscapes (e.g., Daigle, ), research into the specific impacts upon indigenous peoples is even more modest (Adam et al ., ; Kneeshaw et al ., ). Such modest research focuses on impacts, without addressing the truly challenging problem of restricting public access on what in Canada are usually “public” lands.…”
Section: Management Implicationsmentioning
confidence: 92%
See 1 more Smart Citation
“…() with the Kitcisakik Nation in Quebec found concerns similar to those of Saulteau and West Moberly First Nations regarding the impacts of roads within culturally important territory. While modest research has examined in general the impacts of roads in various landscapes (e.g., Daigle, ), research into the specific impacts upon indigenous peoples is even more modest (Adam et al ., ; Kneeshaw et al ., ). Such modest research focuses on impacts, without addressing the truly challenging problem of restricting public access on what in Canada are usually “public” lands.…”
Section: Management Implicationsmentioning
confidence: 92%
“…Other issues are almost never articulated from an indigenous perspective in the forestry literature. The question of access is becoming a growing issue for indigenous peoples, not just in terms of getting into an area (the normal discussion) but in terms of restricting the access of the non‐indigenous to critical areas of their territories, in addition to restricting allocation of natural resources such as wildlife to them (Adam et al ., ). Inconsiderate, competing users, such as unethical hunters and ATV users, threaten both cultural activities (spiritual sites lose their essential nature when surrounded by engine noise) and ecological values (habitat is rendered unusable for species or species are extirpated).…”
Section: Management Implicationsmentioning
confidence: 97%
“…Although increased access to territory might seem a positive outcome for Aboriginal people (facilitating access to hunting grounds), road building contributes to the deterioration of forest ecosystems (Trombulak and Frissell 2000) and has both positive and detrimental impacts on Aboriginal people (Kneeshaw et al 2010, Adam et al 2012. For example, Adam et al (2012) showed that road networks created inter-community tensions as knowledge and access to the land were no longer dependent on traditional cultural norms. Furthermore, increased access to the territory by non-aboriginal users can cause conflicts with Aboriginal people (Kneeshaw et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It also gives access to territories that primary and secondary were previously inaccessible to forest users, thus increasing the potential for roads (km) conflicts between Aboriginal people and other users (Kneeshaw et al 2010, Adam et al 2012.…”
Section: Spatial Configuration Of the Cohortsmentioning
confidence: 99%
“…Moreover, differences in worldviews between Indigenous communities and the industry is another important factor to consider (Booth and Skelton 2011). While communities see themselves as part of the land and their culture is intertwined with the land (Adam et al 2012), corporations, as well as mainstream society, often see themselves as external to forest ecosystems from which they mainly extract resources and acquire economic benefits. Generally, the industry is focused on the forest economic dimension while Indigenous economic development must support community economic, social, environmental and cultural values (Maclean et al 2015).…”
Section: Introductionmentioning
confidence: 99%